Infective Vaginal Discharge among Women of the Reproductive Age in the Outpatient Department of a Primary Care Centre - Shailaja Khadka; Ratna Khatri; Raina Chaudhary (Journal of Nepal Medical Association, 2024)
Introduction: Infective vaginal discharge is the most common complaint of the women of reproductive age group attending gynaecology outpatient department. Vaginal discharge may be normal or abnormal. Infective vaginal discharge is usually related to one of the three conditions, like bacterial vaginosis, vulvovaginal candidiasis, and trichomoniasis. This study aimed to find out the prevalence of infective vaginal discharge among women of the reproductive age in the outpatient department of a primary care centre.